O diário de aprendizagem de língua estrangeira (inglês) sob a perspectiva do processo discursivo - Valdeni da Silva Reis (2007)
The aim of this study is to investigate and comprehend learners journals written by students of English as a foreign language from a university in Minas Gerais. In this research we work within an interdisciplinary approach that includes questions and concepts from Applied Linguistics problematized by a French Discourse Analysis School whose perspective is the consideration that the subject and the meanings of their writings are socio-historically and ideologically constituted in concurrent processes. This study focuses on the reflective task assigned to this instrument in the second or foreign language classroom. In this study we consider the written and spoken facts as imaginary representations. In this perspective, we analyse the representations the learners have of their place and their learning; as well as their teachers place and the learning process through discursive resonances. That means that it is possible to gather expressive recurrences which allow us to infer discursive formations (DF),understood as enunciative regularities within a field of knowledge. We gather our corpus with journals and interviews held with undergraduate learners and extra-mural learners of a state university. In the analysis, interpretation gestures of the learners show recurrences that areexpected and predictable according to the learners historically built place. However, we can also point out some learners singular positions in their journals that break away from the predictable and circular movement of the representations.